PENGARUH POLA ASUH ORANG TUA SUKU BATAK TERHADAP PERILAKU AGRESIF PADA ANAK USIA5-6 TAHUN DI TK NAFIRI KASIH KECAMATAN TAPUNG HULU KABUPATEN KAMPAR - Sipayung, Elsa Yuliana; Chairlsyah, Daviq; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by children who have physical and verbal attacking behavior towards others, especially their peers. This behavior is often referredas aggressive behavior. Parents as the main players in the growth and development of children have the responsibility to care for, guide and improve children's behavior as a function and role that mustbe carried out. This study aimsto determine the effect of parental care of the Batak tribe on aggressive behavior in children aged 5-6 years in Nafiri Kasih Kindergarten, Tapung Hulu District, Kampar Regency. This research is quantitative research with correlational research type. The population in this study was 40 children. The data collection technique used was the observation and distribution of questionnaires. The data analysis technique in this study was the Chi Square correlational technique using the SPSS program ver. 25. From the results of data analysis obtained Chi Square coefficient 0,000 <0.05, with the determinant coefficient value KD = x 100 = x 100 = 43,82. It can be concluded that there is an influence between parenting style of the Batak tribe towards aggressive behavior in children aged 5-6years in Nafiri Kasi Kindergarten, Tapung Hulu District, Kampar Regency by 43.82%.KeyWords: Parenting Batak Parents, Aggressive Behavior